Tunisian Multicenter Study on the Prevalence of Colistin Resistance in Clinical Isolates of Gram Negative Bacilli: Emergence of Escherichia coli Harbouring the mcr-1 Gene - Sana Ferjani; Elaa Maamar; Asma Ferjani; Khaoula Meftah; Hager Battikh; Besma Mnif; Manel Hamdoun; Yosra Chebbi; Lamia Kanzari; Wafa Achour; Olfa Bahri; Adenene Hammami; et al. (Antibiotics, 2022)
Background: Actually, no data on the prevalence of plasmid colistin resistance in Tunisia are available among clinical bacteria. Objectives: This study aimed to investigate the current epidemiology of colistin resistance and the spread of the mcr gene in clinical Gram-negative bacteria (GNB) isolated from six Tunisian university hospitals. Methods: A total of 836 GNB strains were inoculated on COL-R agar plates with selective screening agar for the isolation of GNB resistant to colistin. For the selected isolates, mcr genes, beta-lactamases associated-resistance genes and molecular characterisation were screened by PCRs and sequencing. Results: Colistin-resistance was detected in 5.02% (42/836) of the isolates and colistin-resistant isolates harboured an ESBL (blaCTX-M-15) and/or a carbapenemase (blaOXA-48, blaVIM) encoding gene in 45.2% of the cases. The mcr-1 gene was detected in four E. coli isolates (0.59%) causing urinary tract infections and all these isolates also contained the blaTEM-1 gene. The blaCTX-M-15 gene was detected in three isolates that also carried the IncY and IncFIB replicons. The genetic environment surrounding the mcr-carrying plasmid indicated the presence of pap-2 gene upstream mcr-1 resistance marker with unusual missing of ISApl1 insertion sequence. The Conclusions: This study reports the first description of the mcr-1 gene among clinical E. coli isolates in Tunisia and provides an incentive to conduct routine colistin susceptibility testing in GNB clinical isolates.